Development of ecological tourism in Kazakhstan (Journal of Geography and Environmental Management, 2016)
The basic characteristics of ecological tourism, the dynamics of special-guarded territories of republican meaning incensement and quantity of excursions and also the perspectives of ecological tourism development in Kazakhstan are depicted in the article.
Keywords: eco-tourism; protected areas; tours; ecotourism